Deteksi dini faktor resiko kanker payudara pada wanita di wilayah kerja Puskesmas Batoh Banda Aceh - Nurleli Nurleli; Ainal Mardhiah; Lathifah Hanum (Jurnal SAGO Gizi dan Kesehatan, 2021)
Background: Breast cancer is an abnormal growth of cells that form in breast tissue. In Aceh, breast cancer is the third most non-communicable disease with most breast cancer patients having a period of late treatment. The results of research on women in Lueng Bata District Banda Aceh City in 2015 found data that the majority of respondents had never had regular breast examinations. This can result in breast cancer being detected at an advanced stage where the therapy often cannot make the patient recover and end up in pain and death. To prevent the occurrence of these problems, health promotion is held about breast cancer and breast self-examination (BSE).Objectives: This study aims to increase women's knowledge and understanding of breast cancer and increase awareness for early detection and appropriate treatment.Methods: was carried out for 3 days from 12 to 14 September 2018 to the community in the work area of the Batoh Health Center in Banda Aceh. The method used is filling out questionnaires, lectures accompanied by questions and answers to explain risk factors, early signs of breast cancer, as well as demonstrations of breast self-examination.Results: From the evaluation of the results obtained from the community service activities, among others, is to increase awareness and understanding of the community, especially women about breast cancer and breast self-examination. It is thus expected to continue on a will that is applied in daily behavioral changes to prevent and routinely examine breast cancer in order to prevent complications and improve quality of life.Conclusion: There is an increase in knowledge and understanding of the meaning, risk factors, early signs and symptoms of breast cancer, and how to detect breast cancer early.